LPG gas sensing performance of the SnO2 thin films influenced by the dielectric and conducting properties - Amit Tanwar; Rashmi Menon; Maya Verma; Sandeep Mahajan; Divya Haridas (Discover Applied Sciences)
Abstract This study presents a comprehensive investigation of the dielectric properties and DC conductivity of three tin (IV) oxide (SnO2) thin films with varying thicknesses 30 nm, 90 nm, and 150 nm and explores their influence on gas sensing performance. The gas sensing response of the three SnO2 sensor structures were evaluated for detecting 300 ppm of liquefied petroleum gas (LPG). X-ray diffraction (XRD) and atomic force microscopy (AFM) were used to study the structural and morphological properties of SnO2 thin films. The results of these studies were subsequently correlated to achieve a deeper insight into the gas sensing phenomenon. The dielectric analysis revealed that the SnO2 thin film of 90 nm thickness exhibited the lowest value of dielectric constant ε′(ω), measuring 2.7 at 1 kHz. To gain deeper insights, the capacitance (Cp) of the 90 nm SnO2 thin film was analyzed across a frequency range from 100 Hz to 1 MHz. Pronounced frequency dispersion was observed at elevated temperatures, which was attributed to the presence of a surface barrier. The DC conductivity (σdc) of all the SnO2 thin films was found to be relatively low, approximately 1.7 × 10⁻⁷ Ω⁻1 cm⁻1. The decreased conductivity indicates a high concentration of adsorbed oxygen on the surface and grain boundaries, which traps free electrons and lowers the number of charge carriers. Such characteristics are significant for gas sensing applications, as they can enhance the sensitivity of the sensor by facilitating a pronounced change in conductivity upon exposure to target gases.